Unggas Organik : Peternakan Ayam Masa Depan - M.H. Abbas (Universitas Andalas, 2011)
In response to the failure of the Green Revolution which led to leveling off land productivity, damage the environment, and income of farmers who did not turn up, then introduction the sustainable agriculture development, namely how to manage farms to maintain long-term stability of ecology, biodiversity and improving local wisdom through integrated farming, biotechnology, holistic management, organic farming, animal husbandry based on the principles of animal welfare, food safety and other organics. The insistence of global issues concerning animal walfare, back to nature, low fat, low cholesterol, presence of residual effects, antibiotics, hormones and other additives in food, can direct our movement towards organic poultry, especially with the utilization of native chicken, because potential indigenous chicken and maintenance system is suitable for conversion into the provision of organic chicken production in accordance to environmental sustainability without using feed ingredients which are modified gene. Facing the era of organic poultry, local chicken can be relied upon by Indonesia in the future because it has many advantages; great potential and wide spread among the farmers, have the power of adaptation to local environments is high, tolerant of low quality feed, more tolerant to disease, however; productivity is still low, there is no adequate system poultry breeding. Through an integrated farming organic poultry feed ingredients in the environment can take advantage of farmers, non-conventional waste; earthworms, slugs, snails, waste oil, cattle (rumen contents), forestry, and other nutritious enough. Required number of strategies for the development of local and broiler chickens on a small scale as organic poultry in the future, namely; immediately apply Permentan No. 49/2006 regarding poultry breeding, empowerment of farmers will add value compared to traditional organic poultry, lack of regulation and control of organic poultry, there is need for an organic chicken farmer associations as container consultancy, mentoring, education, technological innovation, joint marketing, and protecting the interests of members , as well as empowerment and awareness by consumers willing to pay more to the advantage of organic chicken.